Biomimicking Fiber Scaffold as an Effective In Vitro and In Vivo MicroRNA Screening Platform for Directing Tissue Regeneration. Issue 9 (27th February 2019) - Zhang, Na; Milbreta, Ulla; Chin, Jiah Shin; Pinese, Coline; Lin, Junquan; Shirahama, Hitomi; Jiang, Wei; Liu, Hang; Mi, Ruifa; Hoke, Ahmet; Wu, Wutian; Chew, Sing Yian
Abstract: MicroRNAs effectively modulate protein expression and cellular response. Unfortunately, the lack of robust nonviral delivery platforms has limited the therapeutic application of microRNAs. Additionally, there is a shortage of drug‐screening platforms that are directly translatable from in vitro to in vivo. Here, a fiber substrate that provides nonviral delivery of microRNAs for in vitro and in vivo microRNA screening is introduced. As a proof of concept, difficult‐to‐transfect primary neurons are targeted and the efficacy of this system is evaluated in a rat spinal cord injury model. With this platform, enhanced gene‐silencing is achieved in neurons as compared to conventional bolus delivery ( p < 0.05). Thereafter, four well‐recognized microRNAs (miR‐21, miR‐222, miR‐132, and miR‐431) and their cocktails are screened systematically. Regardless of age and origin of the neurons, similar trends are observed. Next, this fiber substrate is translated into a 3D system for direct in vivo microRNA screening. Robust nerve ingrowth is observed as early as two weeks after scaffold implantation. Nerve regeneration in response to the microRNA cocktails is similar to in vitro experiments. Altogether, the potential of the fiber platform is demonstrated in providing effective microRNA screening and direct translation into in vivo applications. Abstract : In this work, a fiber substrate for microRNA screening is introduced. Neuronal transfection and spinal cord injury treatment are targeted as a proof of concept. With this platform, extensive microRNA screening is performed and robust nerve ingrowth is observed after scaffold implantation in vivo. Altogether, this fiber platform provides effective microRNA screening and can be directly translated into in vivo applications.